Using the astm e 274 skid trailer data to characterize pavement friction behavior with respect to the traveling speed and the wheel slip ratio (2012)
Knowing the 3-D behavior of friction coefficient (µ) vs. traveling speed (v) and wheel slip ratio (s) on runway and highway pavements can facilitate the modern pavement engineers’ job to a great extent. However, current methodology is limited to measuring µ at desired v and predicting it at different s values (at the same measured v) using 2-dimensional models. The paper presents a study carried out with friction data collected using Locked Wheel Skid Trailer (LWST) (ASTM E 274 Standard Test Method), to obtain the 3-D behavior of µ vs. v and s. An available 3-D friction model which is a combination of two well known 2-D friction models; Pennsylvania State University (PSU) model and Rado model, was used with LWST data collected in a field test on a wet asphalt pavement. The findings suggest that this method can provide reasonable predictions of µ for pavement management purposes.